Delivery and neonatal outcomes of pregnant women during the Shanghai lockdown: A retrospective analysis - Zhou, Fang-Yue; Li, Cheng; Qin, Kai-Zhou; Luo, Chuan; Huang, He-Feng; Wu, Yan-Ting (Frontiers in Pediatrics, 2023)
Objectives: Shanghai witnessed an unprecedented outbreak of COVID-19 and experienced a strict lockdown from March 28, 2022 to May 31, 2022. Most studies to date are on the first lockdown after the outbreak in December 2019. This study aimed to examine the impact of lockdown on delivery and neonatal outcomes among uninfected pregnant women in the new phase of the COVID-19 outbreak. Methods: A retrospective analysis was conducted in the Obstetrics and Gynecology Hospital of Fudan University. Pregnant women without COVID-19 who delivered from March 28, 2022 to May 31, 2022 (lockdown group) and the same period in 2021 (non-lockdown group) were recruited for this study. Logistic regression models and 1:1 propensity score matching (PSM) were used to assess the effect of lockdown on delivery outcomes. Results: A total of 2962 patients were included in this study, 1339 of whom were from the lockdown group. Compared with the non-lockdown group, pregnant women giving birth during lockdown had an increased risk of term prelabor rupture of membranes (TPROM) (aOR = 1.253, 95% CI: 1.026-1.530), and decreased risks of postpartum hemorrhage (PPH) (aOR = 0.362, 95% CI: 0.216-0.606) and fetal malformation (aOR = 0.309, 95% CI: 0.164-0.582). The risk of large for gestational age (LGA) (aOR = 0.802, 95% CI: 0.648-0.992) and rate of admission to the neonatal intensive care unit (NICU) (aOR = 0.722, 95% CI: 0.589-0.885) also significantly declined. After 1:1 PSM, the impact of lockdown on the risk of TPROM (aOR = 1.501, 95% CI: 1.083-2.080), PPH (aOR = 0.371, 95% CI: 0.211-0.654), fetal malformation (aOR = 0.332, 95% CI: 0.161-0.684), LGA (aOR = 0.749, 95% CI: 0.594-0.945) and rate of admission to the NICU (aOR = 0.700, 95% CI: 0.564-0.869) all remained. There were no other delivery or neonatal outcomes affected by the lockdown after the COVID-19 outbreak. Conclusion: This study indicated a significant increase in the risk of term PROM, significant decreases in the risk of PPH, fetal malformation and LGA, and a marked decline in the rate of admission to the NICU during Shanghai Lockdown.